FUNGSI, TUJUAN DAN BENTUK-BENTUK PROMOSI - Lucy Indria Sari; Aisatun Nisa Fauziah; Ludina Risha Novia Arum Putri (Dar El-Falah, 2024)
Promotion is a form of marketing communication that seeks to disseminateinformation, influence or persuade and remind the target market of thecompany and its products to be willing to accept, buy and be loyal to theproducts offered by the company concerned. The main functions ofpromotion activities are: (1) seeking and getting the attention of prospectivebuyers, (2) creating and cultivating "interest" in prospective buyers, (3)developing a sense of wanting prospective buyers to own the goods offered.The promotion objectives are: (1) providing information, (2) increasingsales, (3) positioning the product, (d) forming a product image. There arethree forms of promotion, namely: (1) advertising, (2) sales promotion, (3)personal selling.